Prognostic factors associated with mortality of drug-resistant Acinetobacter baumannii ventilator-associated pneumonia - Juthamas Inchai (2018)
© 2015 Inchai et al. Background: Ventilator-associated pneumonia (VAP) caused by drug-resistant Acinetobacter baumannii is associated with high mortality in critically ill patients. We identified the prognostic factors of 30-day mortality in patients with VAP caused by drug-resistant A. baumannii and compared survival outcomes among multidrug-resistant (MDR), extensively drug-resistant (XDR) and pandrug-resistant (PDR) A. baumannii VAP.Methods: A retrospective cohort study was conducted in the Medical Intensive Care Unit at Chiang Mai University Hospital, Thailand. All adult patients diagnosed with A. baumannii VAP between 2005 and 2011 were eligible. Univariable and multivariable Cox's proportional hazards regression were performed to identify the prognostic factors of 30-day mortality.Results: A total of 337 patients with microbiologically confirmed A. baumannii VAP were included. The proportion of drug-sensitive (DS), MDR, XDR, and PDR A. baumannii were 9.8%, 21.4%, 65.3%, and 3.6%, respectively. The 30-day mortality rates were 21.2%, 31.9%, 56.8%, and 66.7%, respectively. The independent prognostic factors were SOFA score > 5 (hazard ratio (HR) = 3.33, 95% confidence interval (CI) 1.94-5.72, P < 0.001), presence of septic shock (HR = 2.66, 95% CI 1.71-4.12, P < 0.001), Simplified Acute Physiology Score (SAPS) II > 45 (HR = 1.58, 95% CI 1.01-2.46, P = 0.045), and inappropriate initial antibiotic treatment (HR = 1.53, 95% CI 1.08-2.20, P = 0.016).Conclusions: Drug-resistant A. baumannii, particularly XDR and PDR, was associated with a high mortality rate. Septic shock, high SAPS II, high SOFA score, and inappropriate initial antibiotic treatment were independent prognostic factors for 30-day mortality.